The spider genus Pseudotyphistes (Araneae, Linyphiidae) in Uruguay: a new species and new records - Cajade, Manuel; Laborda, Álvaro; Hagopián, Damián; Simó, Miguel (Zootaxa, 2023)
Pseudotyphistes deinceps Cajade n. sp. is described from Uruguay based on males and females. Illustrations of somatic and sexual characters and a distribution map of the species is provided. In addition, new records of Pseudotyphistes pennatus Brignoli, 1972 for the country are presented. Data of the natural history and conservation status of both species are discussed.